Orbital and electronic responses in the GaN/AlN quantum structures constructed on different crystal planes. (1st July 2022) - Yan, Jinjian; Chen, Xinlu; Kang, Wenyu; Li, Shuping; Kang, Junyong; Lin, Wei
Abstract: This work used the first-principles simulations to investigate interactions between orbital and electronic properties in the GaN m /AlN n quantum structure. By rotating the quantum well plane 90˚ from the c -plane, we delineated responses including a uniform bond length, an equal charge distribution on both well sides, and orbital changes at the quantum level near the valence band maximum (from the degenerated p x / p y to the separated p y and p z ). The found responses would positively contribute to wavelength reduction, quantum efficiency, and surface-emitting geometry. The tunable bandgap enables the production of electro-optic devices of Al-rich AlGaN for DUV applications.